Simulation-oriented Transformation of CAD Models. Issue 3 (3rd May 2016) - Andrae, René; Köhler, Peter
ABSTRACT: Computations and simulations during the design process are performed with a variety of Computer-Aided Design (CAD) systems. For the integration of analytical calculation methods, KBE (Knowledge-Based Engineering) approaches have been integrated quite successfully. This is particularly true for parameter-oriented inference mechanisms. Numerical methods require further developed methods especially in the consolidation between design and simulation models. This paper presents a methodological approach that automates the model transformation from the design to simulation environment. This approach bases upon so-called "smart" component models, which are processed rule-based and are enriched with component-specific knowledge for the integration of design, computation and simulation. By using simulation-oriented features and components, the preprocessing becomes more efficient. GRAPHICAL ABSTRACT: